New security dimensions in the Asia–Pacific - Desker, Barry (2022)
The rise of China provides a major challenge to the United States, the undisputed hegemon in the Asia-Pacific region since the second world war. This development provides regional states with an opportunity to shape the regional security architecture by adopting an inclusive approach to China. The role of the Association of Southeast Asian States (ASEAN) tends to be under-estimated by Western scholars who often see the European model as the only approach to regional integration. This paper discusses the significant achievements of ASEAN in serving as a catalyst for the establishment of regional institutions. Such institutions could serve as instruments for the management of China's relations with Japan and India. It is contended that the emergence of Asian powers, especially China, will result in a challenge to the Washington Consensus of Western norms and values focusing on individual rights which have governed international institutions. The rise of China is likely to see the application of a Beijing Consensus emphasising the balance between individual rights and social obligations, which would resonate positively in the region. In the twenty-first century, global institutions will need to reflect the norms, values and practices of global society and not just Atlantic perspectives.